Occupational sharps injury management in Malaysia : a narrative overview - Abdullah Aliff Abdul Wahab; Rosnah Ismail; Halim Ismail (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Occupational sharps injury remains a never-ending issue faced by healthcare workers (HCWs). There were several types of post-exposure management available in Malaysia. Thus, it was hoped that this narrative overview could provide an impetus towards the understanding of post-exposure management in our local healthcare setting. Working in a healthcare setting, sharps appeared to be an inevitable hazard faced every day by individual HCWs. While PEP was available for HIV and Hepatitis B, none was available for Hepatitis C. Despite that, the latter seemed to have curative treatment for it. Conclusion: Overall, most literatures had showed the benefits of adherence to post-exposure follow-up management, particularly when PEP was indicated. Occupational sharps injury remains a never-ending issue faced by healthcare workers (HCWs). There were several types of post-exposure management available in Malaysia. Thus, it was hoped that this narrative overview could provide an impetus towards the understanding of post-exposure management in our local healthcare setting. Working in a healthcare setting, sharps appeared to be an inevitable hazard faced every day by individual HCWs. While PEP was available for HIV and Hepatitis B, none was available for Hepatitis C. Despite that, the latter seemed to have curative treatment for it. Conclusion: Overall, most literatures had showed the benefits of adherence to post-exposure follow-up management, particularly when PEP was indicated. Occupational sharps injury remains a never-ending issue faced by healthcare workers (HCWs). There were several types of post-exposure management available in Malaysia. Thus, it was hoped that this narrative overview could provide an impetus towards the understanding of post-exposure management in our local healthcare setting. Working in a healthcare setting, sharps appeared to be an inevitable hazard faced every day by individual HCWs. While PEP was available for HIV and Hepatitis B, none was available for Hepatitis C. Despite that, the latter seemed to have curative treatment for it. Conclusion: Overall, most literatures had showed the benefits of adherence to post-exposure follow-up management, particularly when PEP was indicated.